Reconsidering Justice for Female Victims of Intimate Partner Violence: A Sociocultural and Legal Framework - Hakim, Fany Nur Rahmadiana (Deviance Jurnal Kriminologi, 2023)
The pervasive internalization of patriarchal norms within Indonesian society perpetuates the victimization of women, particularly evident in cases of intimate partner violence. This study examines the escalating instances of violence against women within personal relationships, be it in marital or dating contexts. Despite the increasing prevalence of such incidents, the measures employed to address and safeguard victims remain inadequate. This paper employs an explanatory analysis method, focusing on two case studies of intimate partner violence (IPV) in both dating and domestic contexts. Utilizing a criminological framework, the analysis aims to scrutinize the pervasive injustice experienced by a significant portion of the female population. The selected case studies serve as illustrative examples to demonstrate the challenges inherent in the legal process, emphasizing the difficulty in access attributed to a law enforcement perspective that has yet to fully embrace a gender justice worldview. The findings of this study draw attention to the nuanced dynamics surrounding IPV in the legal domain. A crucial aspect highlighted is the need for a comprehensive understanding of these dynamics. The investigation extends to social reactions, with the virtual community, or "netizens," emerging as a significant influencer in shaping the trajectory of IPV cases. The collective voices of netizens are acknowledged for their potential impact on the handling of such cases. The discussion in this paper highlights the factor of injustice faced by the female victims of IPV which is a sociocultural factor specifically the perpetuation of the following: 1) gendered stereotype understanding, and 2) stigmatization and repeat victimization toward the victims. By amplifying the importance of equitable punishment for perpetrators of intimate partner violence, the collective online discourse has the potential to shape societal attitudes and contribute to a more just resolution of these cases. In conclusion, this paper underscores the necessity for transformative changes in legal structures and societal perspectives, as well as the urgency of online advocacy in addressing the persistent issue of IPV and its impact on women's pursuit of justice.